Electrochemically Modulated LiNi1/3Mn1/3Co1/3O2 Cathodes for Lithium‐Ion Batteries. Issue 5 (20th March 2019) - Shuai, Honglei; Li, Jiayang; Hong, Wanwan; Gao, Xu; Zou, Guoqiang; Hu, Jiugang; Hou, Hongshuai; Ji, Xiaobo; Liu, Huiqun
Abstract: Layered lithium transition‐metal oxides are considered as promising cathodes for new‐generation lithium‐ion batteries due to their high capacity and excellent rate capability. Nevertheless, the approach of preparing precursors is generally restricted to the utilization of wet‐chemical methods. Herein, for the first time, an electrochemical strategy is introduced to prepare Ni1/3 Mn1/3 Co1/3 (OH)2 precursor with the mixing at the atomic level by electrochemically anodized Ni–Mn–Co alloy anode, demonstrating the superiorities of high yield without the process of the extreme alkaline environment and complicated process. Furthermore, the layered LiNi1/3 Mn1/3 Co1/3 O2 cathode is obtained through calcining the mixture of precursors and Li sources under a certain calcined temperature. As anticipated, the initial discharge specific capacities of 183.9 mAh g −1 at 0.1 C with a capacity retention of 79.66% after 120 loops are delivered for LiNi1/3 Mn1/3 Co1/3 O2 cathode with calcining at 930 °C, and it also exhibits superior rate capability with specific capacities of 151.1 and 116.5 mAh g −1 at 1 and 10 C, respectively. Therefore, this innovative approach can be readily extended to prepare other types of lithiated transition metal oxide precursors. Abstract : Ni1/3 Mn1/3 Co1/3 (OH)2 precursor is successfully prepared through electrochemically anodized Ni–Mn–Co alloy, and the transition metal ions are homogeneously mixed at the atomic level. LiNi1/3 Mn1/3 Co1/3 O2 cathodes display a well‐ordered layered structure and low cation mixing and show good electrochemical properties for lithium ion batteries (LIBs). This innovative and practicable electrochemical method can be extended to prepare other types of ternary cathode precursors.